Digital inclusion of mature students: Analysis of their attitudes and ICT competences - Padilla-Carmona, M. Teresa; Suárez-Ortega, Magdalena; Sánchez-García, María Fe (Revista Complutense de Educación, 2016)
This research aims to identify the attitudes and competences of mature students regarding information and communication technologies (ICT), with special focus on digital learning platforms and social networks (Web 2.0). In addition, the study tries to assess the influence of several socio-demographic variables (gender and age) in the use of these tools and in the students’ self-perception of their digital competency. The research uses the survey method and a questionnaire has been applied to a sample of 382 students entering the University of Seville via the special routes for older than 25, than 40 and 45 years. Results showed a general positive attitude towards the ICT, which could also be qualified as pragmatic, since the tools are positively valued based on their potential benefits in the learning processes. Results also point to the fact that students have not been specifically trained in the use of ITC. The level of competency that they claim to possess regarding the use of these resources is medium-low. Furthermore, the over 45 year group declare themselves less competent than the over 25 and 40. Finally, some suggestions are given in order to improve the participation of mature students in Higher Education.